GOLD PLACERS IN THE SOUTH OF UKRAINE – CURRENT VIEWS AND PROSPECTS - Lomakin І.; Sarvirov, E.; Kochelab, V.; Medvedskij, R. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The consistently high level of world gold prices against the background of depletion of reserves with easily extracted metal, lead to the need to introduce the industrial development of deposits with low-tech ores and sands. This requires improving the methodology of exploration and the use of efficient technologies for the enrichment and extraction of gold. The article is devoted to an important problem - the question of the real potential of placer gold in the south of Ukraine and its practical significance. An attempt is made on the basis of the analysis of the accumulated geological information to assess the quality of previously obtained results on loose gold of Ukraine. According to geological data, numerous manifestations of loose gold of various scales associated with sedimentary strata of Meso-Cenozoic sediments are widespread on the territory. It is noted that the geological study of placers in Ukraine was suspended during the lowest world gold prices - in the late 90’s of last century - as a result of which many promising areas were left out. The authors refute the assertion that gold deposits on the Ukrainian Shield and in the Northern Black Sea Coast are of no industrial importance due to their low gold content. The negative assessment of placer gold content is due to the shortcomings of the methodology and test methods that were used in the work. The previously used exploratory model of "classic" gold placers does not correspond to the real properties of gold-bearing deposits in the sedimentary stratum. The predominant mass of gold of indigenous springs and placers of Ukraine belongs to small and thin classes of particle size distribution, and gold-bearing deposits have high clay content. In this regard, the deposition of gold occurred, as a rule, not in the subglacial part of the section of river valleys, but in the so-called "oblique" facies, which were almost not studied previously. The test used a mining method of gold extraction, which is not suitable for reliable determination of the gold content of small and fine grades. This led to a systematic underestimation of the gold content in the studied manifestations, as well as a significant reduction in the size of gold deposits. Therefore, a reassessment of previously obtained geological data is needed to determine the objective characteristics of the distribution and actual gold content in placers. Suggestions for further study of placers are given. Modern approaches to forecasting, studying and testing placers are considered, in particular, the use of data from remote sensing of the Earth, GIS-technologies and methods of neotectonic analysis for forecasting and searching for placers. The need to use separate determination of gold content depending on the particle size is emphasized.